EXPERIMENTAL SUBSTANTIATION OF INFLUENCE OF ROTATIONAL MECHANISMS ON WAVE FORMATION OF AN EARTH’S CRUST - SIVAK, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The experimental ground of the rotation mechanism technogenesis is considered with using the earth’s crust rotation. On the basis of the special carried out experiments it is insisted that earth’s crust can vibrate with frequencies close to its eigenfrequency. On the basis of the obtained investigation results it can foreknow that during the action on the earth crust dynamical loading the vibration amplitude of the earth’s crust increases substantially and as result at the place where indicated loading acts it leads to catastroplic breakdowns.